Drug utilization review of antibiotic agents in community acquired pneumonia inpatients of a tertiary hospital - Gamboa, Paolo Roliz S.
Antimicrobials are crucial in treating bacterial infections like pneumonia which remains a leading cause of mortality. However, its misuse has increased resistance, driven by ineffective infection control, substandard drugs, poor compliance, and inappropriate prescribing. This study evaluated the utilization of antimicrobials for community acquired pneumonia (CAP) inpatients. This study implemented a non-experimental, retrospective, cross-sectional records review of patients diagnosed with moderate (MR) and high risk (HR) CAP admitted to the tertiary hospital during 2022. Patient characteristics and antimicrobial utilization were described using univariate analysis and defined daily dose per 1000 inhabitants per day (DiD), respectively. Associations of drug therapy problems with mortality, clinical cure, length of hospital stay, and medication costs were analyzed using regression analysis. Among the eligible patient charts (n=78), most were found to be older males with circulatory comorbidities (CAP-MR=76.36%; CAP-HR=65.22%), with a number of patients (CAP-MR=45.45%; CAP-HR=21.74%) not undergoing culture tests. However, in the cohort of Multidrug Resistant Organism (MDRO) cases, risk for Extended-spectrum beta-lactamase (ESBL) was the most prevalent for CAP-MR (14.55%), while risk for P. aeruginosa for CAP-HR (34.78%). Oral Azithromycin was the most consumed (549.33 DiD), followed by Ceftriaxone (297.60 DiD) and Piperacillin-Tazobactam (245.19 DiD). Drug selection was the most prevalent problem (CAP-MR=68.67%; CAP-HR=78.79%) showing that physicians prescribe differently from the guidelines. Higher mean total medication costs were observed for CAP-HR (₱27,044.37) than CAP-MR (₱9,511.75). Positive associations were found between total medication costs and the number of unique antibiotics (p=0.001); the length of hospital stay with the number of unique antibiotics (p=0.003); and total medication costs with the length of hospital stay (p=0.039). Thus, CAP remains a critical health concern, complicated by drug therapy problems. These findings underscore the significance of rational medicine use—emphasizing the necessity for meticulous antibiotic management and relevant restrictions to improve patient outcomes and reduce healthcare costs.